1977
DOI: 10.1172/jci108641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of somatostatin on splanchnic glucose metabolism in postabsorptive and 60-hour fasted humans.

Abstract: A B S T R A C T Cyclic somatostatin was administered intravenously (10 ,ug/min for 60 min) to 10 healthy overnight fasted (postabsorptive) subjects and to 5 healthy 60-h fasted subjects. In both groups, arterial insulin and glucagon fell 50%o and splanchnic release of these hormones was inhibited. In the overnight fasted subjects splanchnic glucose output fell 70%, splanchnic uptake of lactate and pyruvate was unchanged, alanine uptake fell by 25%, and glycerol uptake rose more than twofold in parallel with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(56 citation statements)
references
References 33 publications
5
50
1
Order By: Relevance
“…If glucose production was greater during initial period of fasting, the contribution of GNG would be higher. Balance studies do not show sufficient uptake of substrate by the splanchnic bed to account for 64 % production (Wahren et al 1977).…”
Section: Nmr Spectroscopymentioning
confidence: 97%
See 1 more Smart Citation
“…If glucose production was greater during initial period of fasting, the contribution of GNG would be higher. Balance studies do not show sufficient uptake of substrate by the splanchnic bed to account for 64 % production (Wahren et al 1977).…”
Section: Nmr Spectroscopymentioning
confidence: 97%
“…In the first method concentrations across the liver of blood lactate, pyruvate, glycerol and GNG amino acids, as well as glucose, together with blood flow, are measured. The fractional contribution of GNG to glucose production is then calculated, assuming all the GNG substrates taken up are converted to glucose (Wahren et al 1977). Thus, estimates are maximal, except that a proportion of GNG substrates are produced and converted to glucose within the liver.…”
Section: H-labelled Water: Gluconeogenesis: Stable Isotopes: Nmr: Masmentioning
confidence: 99%
“…The principle organ for regulating blood glucose is the liver, which in the face of increased blood glucose disposal will increase the rate of hepatic glucose production through glycogen catabolism and gluconeogenesis (Ahlborg et al 1974, Wahren et al 1977. Ahlborg & Felig (1982) reported that during prolonged moderate intensity exercise (w60% VO 2max ), the rate of hepatic glucose output barely matched the rate of leg glucose uptake during the first 40 min of exercise.…”
Section: Figurementioning
confidence: 99%
“…10) whereas, in 60 h fasted subjects, the hypoglycaemic effect was also due to suppression of gluconeogenesis [106]. The hyperglycaemia accompanying prolonged infusion of somatostatin was due partially to increased hepatic glucose output, and partially to decreased peripheral uptake of glucose [97].…”
Section: On Endocrine Functionsmentioning
confidence: 99%